Quality determination method of mixed cement for low carbon type concrete, and method for manufacturing mixed cement for low carbon type concrete

The method predicts the 28-day mortar compressive strength of mixed cement for low-carbon concrete by correlating physical property values with calibration curves, addressing inaccuracies in existing quality determination methods and ensuring precise strength development.

JP2025006785AActive Publication Date: 2025-01-17SUMITOMO OSAKA CEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023107772
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Existing methods for determining the quality of mixed cement for low-carbon concrete are inaccurate and lack precision in estimating strength development, particularly when color tones of mixed materials are similar, leading to difficulties in quality control.

Method used

A method that predicts the 28-day mortar compressive strength of mixed cement by correlating physical property values such as one-day strength, hydration reaction rate, and cumulative calorific value with calibration curves, using accelerated curing by heating to determine the quality of mixed cement containing 0-55% Portland cement and 45-99% mixed materials.

Benefits of technology

Enables rapid and accurate quality determination of mixed cement for low-carbon concrete, ensuring the 28-day mortar compressive strength is within acceptable limits, thereby improving the precision of quality control.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006785000003
    Figure 2025006785000003
  • Figure 2025006785000004
    Figure 2025006785000004
  • Figure 2025006785000005
    Figure 2025006785000005
Patent Text Reader

Abstract

To provide a quality determination method capable of confirming 28-day mortar compression strength of mixed cement for low carbon type concrete within a short period, and a method for manufacturing mixed cement for low carbon type concrete using the quality determination method.SOLUTION: A quality determination method of mixed cement for low carbon type concrete having a content of Portland cement in mixed cement of more than 0 mass% and 55 mass% or less, in which the mixed cement contains Portland cement and a mixed material, and has a correlation between 28-day mortar compression strength (Y) of a plurality of mixed cement for a calibration curve having a changed content ratio of the mixed material and 28-day mortar compression strength (Y) of the mixed cement for the calibration curve, wherein the method previously determines a relational expression with a physical property value (X) of the mixed cement for the calibration curve accelerated and cured by heating, and determines a physical property value (X) of mixed cement for low carbon type concrete of a sample to be inspected.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for evaluating the quality of a mixed cement for low-carbon concrete and a method for producing a mixed cement for low-carbon concrete. [Background technology]

[0002] Climate change is becoming a serious problem on a global scale, and various concrete measures to reduce carbon dioxide emissions are being considered. In the construction industry, cement production is said to generate a large amount of carbon dioxide, most of which is emitted during the burning process of clinker, the main component of cement. Therefore, attention has been focused on various low-carbon cements that reduce the proportion of clinker in cement and instead increase the proportion of by-products such as ground granulated blast furnace slag and fly ash, which are mixed materials, and concrete made using these cements is gradually becoming more widespread.

[0003] These blended cements can be manufactured either by mixing cement and mixing materials at a ready-mix concrete plant to produce ready-mix concrete, or by premixing cement at a mixing plant and shipping it to the ready-mix concrete plant. In the former case, it is difficult to actually implement due to restrictions on facilities and space, such as the need for separate silos to store each material. The latter is rational because it allows for a high degree of freedom in the manufacture of premixed cement that meets the user's needs and can be shipped to ready-mix concrete plants. However, for mixed cement with a high proportion of admixtures, variations in the mixture ratio have a large effect on physical properties, particularly early strength development, so a quality confirmation method was needed that could quickly determine whether the manufactured cement had the desired composition and had the appropriate strength development.

[0004] In response to such demands, for example, a method for determining whether the mixing ratio of blended cement is a specified amount is known in which the color tone of the blended cement is measured and whether the mixed materials have been mixed in the specified amounts is estimated (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6198143 Summary of the Invention [Problem to be solved by the invention]

[0006] The assessment method described in Patent Document 1 allows for rapid measurement, but it has the drawbacks of making it difficult to estimate the blending amounts when there is no difference in color between the mixed materials, and because it is not an actual control method for standard strength, it does not provide sufficient accuracy for strength control, and therefore a new quality control method was desired. The present invention aims to provide a quality assessment method for low-carbon mixed cement for concrete, which enables confirmation of the 28-day mortar compressive strength of the low-carbon mixed cement for concrete in a short period of time, and a method for producing the low-carbon mixed cement for concrete using the quality assessment method. [Means for solving the problem]

[0007] The present invention relates to the following <1> ~ <10> to provide. <1> A method for evaluating the quality of a low-carbon mixed cement for concrete, the mixed cement having a Portland cement content of more than 0% by mass and not more than 55% by mass, comprising: The 28-day mortar compressive strength (Y) of a plurality of calibration curve mixed cements containing the Portland cement and the mixed material and varying the content ratio of the mixed material; A correlation equation is previously obtained between the 28-day mortar compressive strength (Y) of the calibration curve mixed cement and the physical property value (X) of the calibration curve mixed cement accelerated cured by heating, A quality assessment method for low-carbon mixed cement for concrete, comprising: determining a physical property value (X) of a test sample of low-carbon mixed cement for concrete, predicting the 28-day mortar compressive strength (Y) of the test sample, and assessing the quality of the test sample of low-carbon mixed cement for concrete by comparing the 28-day mortar compressive strength (Y) of the test sample with a control level value of the 28-day mortar compressive strength.

[0008] <2> The physical property value (X) is measured by mixing a hardening accelerator into the calibration curve mixed cement and the test sample low-carbon concrete mixed cement. <1> A method for evaluating the quality of the low-carbon mixed cement for concrete described in claim 1.

[0009] <3> The conditions for accelerated curing of the mixed cement for the calibration curve by heating are 30 to 70°C and 6 to 24 hours. <1> or <2> A method for evaluating the quality of the low-carbon mixed cement for concrete described in claim 1.

[0010] <4> The physical property value (X) is at least one selected from the group consisting of (i) one-day strength of mortar accelerated cured by heating, (ii) one-day hydration reaction rate of cement paste accelerated cured by heating, and (iii) one-day accumulated heat generation amount after the start of accelerated curing by heating. <1> ~ <3> A method for evaluating the quality of a mixed cement for low-carbon concrete according to any one of the above.

[0011] <5> The Portland cement is one or more selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement. <1> ~ <4> A method for evaluating the quality of a mixed cement for low-carbon concrete according to any one of the above.

[0012] <6> The mixed material is one or more selected from the group consisting of ground granulated blast furnace slag, fly ash, silica fume, expanding material, and biomass incineration ash. <1> ~ <5> A method for evaluating the quality of a mixed cement for low-carbon concrete according to any one of the above.

[0013] <7> The hardening accelerator is one or more selected from the group consisting of calcium chloride, potassium chloride, sodium chloride, sodium thiocyanate, and calcium formate. <2> A method for evaluating the quality of the low-carbon mixed cement for concrete described in claim 1.

[0014] <8> A method for producing a mixed cement for low-carbon concrete, the mixed cement having a Portland cement content of more than 0% by mass and not more than 55% by mass, comprising: A mixing step of mixing the Portland cement and the mixed material to obtain a low-carbon concrete mixed cement; <1> ~ <7> a quality assessment step of assessing the quality of the low-carbon concrete mixed cement obtained in the mixing step by using the quality assessment method for the low-carbon concrete mixed cement according to any one of the above. A method for producing a low-carbon mixed cement for concrete comprising the steps of:

[0015] <9> The Portland cement is one or more selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement. <8> A method for producing a mixed cement for low-carbon concrete according to the present invention.

[0016] <10> The mixed material is one or more selected from the group consisting of ground granulated blast furnace slag, fly ash, silica fume, expanding material, and biomass incineration ash. <8> or <9> A method for producing a mixed cement for low-carbon concrete according to the present invention. Effect of the Invention

[0017] According to the present invention, there are provided a quality assessment method for low-carbon mixed cement for concrete, which enables confirmation of the 28-day mortar compressive strength of the low-carbon mixed cement for concrete in a short period of time, and a method for producing the low-carbon mixed cement for concrete using the quality assessment method. [Brief description of the drawings]

[0018] [Figure 1]1 shows a calibration curve of 28-day mortar compressive strength and accelerated ignition loss prepared in Example 1. [Diagram 2] 1 shows a calibration curve of 28-day mortar compressive strength and accelerated 1-day mortar compressive strength prepared in Example 1. [Diagram 3] 1 shows a calibration curve of 28-day mortar compressive strength and accelerated heat generation in one day, prepared in Example 1. [Figure 4] 1 shows a calibration curve of 28-day mortar compressive strength and accelerated ignition loss prepared in Example 2. [Diagram 5] 1 shows a calibration curve of 28-day mortar compressive strength and accelerated 1-day mortar compressive strength prepared in Example 2. [Figure 6] 1 is a calibration curve of 28-day mortar compressive strength and accelerated heat generation in one day, prepared in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] In this specification, the expression "AA to BB" as a numerical range means "not less than AA and not more than BB."

[0020] <Quality judgment method> The quality assessment method of the present invention is a method for assessing the quality of a mixed cement for low-carbon concrete, the mixed cement having a Portland cement content of more than 0 mass% and not more than 55 mass%, comprising: The 28-day mortar compressive strength (Y) of a plurality of calibration curve mixed cements containing the Portland cement and the mixed material and varying the content ratio of the mixed material; A correlation equation is previously obtained between the 28-day mortar compressive strength (Y) of the calibration curve mixed cement and the physical property value (X) of the calibration curve mixed cement accelerated cured by heating, By determining the physical property value (X) of the test sample of low-carbon mixed cement for concrete, the 28-day mortar compressive strength (Y) of the test sample is predicted, and by comparing the control level value of the 28-day mortar compressive strength (Y) of the test sample with the 28-day mortar compressive strength of the test sample, the quality of the test sample of low-carbon mixed cement for concrete is judged.

[0021] The mixed cement for low-carbon concrete used in this embodiment has a Portland cement content of more than 0 mass% and 55 mass% or less. The mixed material content in the mixed cement is 45 mass% or more and less than 99 mass%. In addition, the "control level value of 28-day mortar compressive strength" means the 28-day mortar compressive strength of a low-carbon concrete blended cement in which the components are mixed in the designed ratio. When designing blended cement, each component can be weighed accurately in a laboratory. However, when producing blended cement at a mixing plant, malfunctions often occur in the equipment that weighs each component, causing the components to not be weighed as designed, resulting in variations in the mixing ratio. Because blended cement for low-carbon concrete contains a small amount of Portland cement, variations in the mixing ratio of Portland cement and the blending materials have a significant effect on physical properties, particularly the development of early strength (28-day mortar compressive strength). Since it is difficult to check the quality of mixed cement (mixed product made using actual equipment) produced at the mixing plant with a 28-day margin before shipping it, a quality assessment method that could check the quality more quickly was desired. The quality assessment method according to the present embodiment, having the above-described configuration, can predict the 28-day mortar compressive strength of a blended cement in a short period of time.

[0022] This is because, by measuring a physical property (X) that can be measured in a short period of time as a physical property that is correlated with the 28-day mortar compressive strength, the physical property (X) can be measured when the mixed cement is shipped. In the present invention, in order to measure the physical property (X) in a short period of time, the mixed cement for the calibration curve is subjected to accelerated curing by heating. In addition, by comparing the 28-day mortar compressive strength predicted by measuring the physical property value (X) with the control level value of the 28-day mortar compressive strength, the quality of the low-carbon mixed cement for concrete of the test sample can be easily judged from the difference in values, etc. The quality assessment method of the present invention for low-carbon mixed cement for concrete does not assess the quality based on the color tone of the mixed cement as described in Patent Document 1, but rather assesses the quality based on physical property values, so that the 28-day mortar compressive strength of the low-carbon mixed cement for concrete can be confirmed more accurately than before. The quality determination method of the present invention will be described in detail below.

[0023] [Mixed cement] The blended cements used in the quality evaluation method of the present invention are the blended cement for the calibration curve and the blended cement for low-carbon concrete as the test sample. Both blended cements contain Portland cement with a content of more than 0 mass% and not more than 55 mass%, and a blended material with a content of 45 mass% or more and less than 99 mass%.

[0024] (Cement blend for calibration curve) The blended cement for the calibration curve is a blended cement for quality assessment used to assess the quality of the test sample blended cement for low-carbon concrete. In order to create a calibration curve, multiple types (e.g., five or more types) are prepared by changing the content ratio of the blended materials. For example, in a blended cement designed to have ordinary Portland cement, mixed material A, and mixed material B at 35 mass%, 40 mass%, and 25 mass%, respectively, in order to obtain a specified strength, the amount of mixed material A can be changed to 30-45 mass%, and mixed material B to 20-35 mass%, etc.

[0025] (Low carbon type concrete blended cement sample under test) The test sample low-carbon mixed cement for concrete is a mixed cement whose quality is assessed by the quality assessment method of the present invention, and is a mixed cement manufactured in a factory or the like. In the quality assessment method of the present invention, the types of components contained in the calibration curve mixed cement and the test sample low-carbon mixed cement for concrete are, in principle, the same as each other. In the above example, the quality assessment method of the present invention assesses the quality of an actual mixture obtained by mixing the components in a factory in the expected mass ratio of ordinary Portland cement, mixed material A, and mixed material B of 35:40:25, and does not intentionally mix components outside the design range.

[0026] Therefore, for example, in the production of a mixed cement designed to contain only ordinary Portland cement, mixing material A, and mixing material B, the mixed cement produced (the test sample mixed cement for low-carbon concrete) should also contain only ordinary Portland cement, mixing material A, and mixing material B, so the mixed cement for the calibration curve to confirm quality should also be prepared with a composition containing only ordinary Portland cement, mixing material A, and mixing material B. However, there is a possibility that components different from the designed composition may be unintentionally mixed into the manufactured blended cement (the test sample blended cement for low-carbon concrete) due to the presence of different types of Portland cement and / or different mixed materials different from the designed composition in the factory equipment. In such a case, the types of components contained in the calibration curve blended cement and the test sample blended cement for low-carbon concrete will be different. Hereinafter, matters simply referred to as "mixed cement" apply to both the mixed cement for the calibration curve and the mixed cement for low-carbon concrete that is the test sample, unless otherwise specified.

[0027] (Portland cement) The Portland cement is not particularly limited, but in low-carbon concrete with a low Portland cement content, from the viewpoint of improving the concrete strength, it is preferable that the Portland cement be one or more selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement. The content of Portland cement in the blended cement is more than 0 mass% and not more than 55 mass%, preferably from 5 mass% to 55 mass%, and more preferably from 10 mass% to 50 mass%. When ordinary Portland cement is used as the Portland cement, the content of ordinary Portland cement in the blended cement is preferably 10% by mass or more and 50% by mass or less, more preferably 15% by mass or more and 50% by mass or less, and even more preferably 20% by mass or more and 45% by mass or less. When using high-early-strength Portland cement as the Portland cement, the content of high-early-strength Portland cement in the mixed cement is preferably 5% by mass or more and 45% by mass or less, more preferably 5% by mass or more and 40% by mass or less, and even more preferably 10% by mass or more and 35% by mass or less.

[0028] (mixed material) The mixed materials are materials that are mixed with Portland cement, other than the hardening accelerator. The hardening accelerator is an agent that can be mixed into the calibration curve blended cement and the test sample low-carbon concrete blended cement in order to measure the physical property value (X) in a short period of time, and is not a component of the blended cement. Specific examples of the mixed material include ground granulated blast furnace slag, fly ash, silica fume, expanding material, biomass incineration ash, etc. Only one type of mixed material may be used, or two or more types may be used. The mixed material is included in the mixed cement in such a range that the content of the mixed material in the mixed cement is 45 mass % or more and less than 99 mass %.

[0029] [Creating a calibration curve] In the quality evaluation method of the present invention, first, a plurality of calibration curve mixed cements with different content ratios of mixed materials are prepared, and the 28-day mortar compressive strength (Y) of each calibration curve mixed cement is measured. Next, a physical property value (X) that is correlated with the 28-day mortar compressive strength (Y) of each calibration curve mixed cement is measured. Here, the physical property value (X) is preferably a physical property value that can be measured in a short period of time, and it is preferable to measure various physical property values ​​at an age of 1 to 3 days, such as mortar compressive strength, integrated heat generation, and hydration reaction rate. In this case, the physical property value (X) can be obtained in a short period of time by heating the mixed cement for accelerated curing. The conditions for accelerated curing are preferably 30 to 70°C and 6 to 24 hours.

[0030] In order to measure the physical property value (X) in a short period of time, the physical property value (X) may be measured by mixing a hardening accelerator into the mixed cement for the calibration curve. Examples of the hardening accelerator include calcium chloride, potassium chloride, sodium chloride, sodium thiocyanate, calcium formate, etc. Only one type of hardening accelerator may be used, or two or more types may be used. When a hardening accelerator is used, the content of the hardening accelerator in the mixture of the mixed cement and the hardening accelerator is preferably 0.5 to 5 mass %, and more preferably 1 to 3 mass %.

[0031] The physical property value (X) is preferably one or more selected from the group consisting of (i) one-day strength of mortar subjected to accelerated curing by heating (one-day mortar compressive strength), (ii) hydration reaction rate of cement paste subjected to accelerated curing by heating after one day, and (iii) accumulated heat generation after one day from the start of accelerated curing by heating. The physical property value (X) to be measured may be one type only, or may be two or more types. Measuring a plurality of physical property values ​​(X) allows for more accurate quality determination. The physical property (X) can easily predict the 28-day mortar compressive strength (Y) of the test sample in a short period of time regardless of whether it is any of (i) to (iii). From the viewpoint of versatility, however, (i) is preferred among (i) to (iii). The 28-day mortar compressive strength (Y) and the 1-day mortar compressive strength, hydration reaction rate, and integrated heat release value as physical property values ​​(X) can be measured by the methods described in the Examples.

[0032] After measuring the 28-day mortar compressive strength (Y) and physical property (X) for multiple calibration curve mixed cements, the measured values ​​for each calibration curve mixed cement are plotted, for example, with the 28-day mortar compressive strength (Y) on the vertical axis and the physical property (X) on the horizontal axis, to obtain a calibration curve.

[0033] On the other hand, for the test sample low-carbon mixed cement for concrete, the same type of physical property value (X) as the physical property value (X) measured using the calibration curve mixed cement is obtained. From the obtained measured values ​​and the calibration curve, the 28-day mortar compressive strength (Y) of the test sample low-carbon mixed cement for concrete can be predicted.

[0034] The physical property value (X) of the test sample of low-carbon mixed cement for concrete is preferably measured in the same manner as the measurement of the physical property value (X) of the calibration curve mixed cement, and it is preferable to measure the physical property value (X) in a short period of time by heating the mixed cement for accelerated curing. The conditions for accelerated curing are preferably 30 to 70°C and 6 to 24 hours. In order to measure the physical property value (X) in a short period of time, the physical property value (X) may be measured by mixing a hardening accelerator with the test sample of low-carbon mixed cement for concrete. The types of hardening accelerators that can be used are as described above.

[0035] Furthermore, the quality of the low-carbon mixed cement for concrete of the test sample can be judged by comparing the predicted value obtained using the calibration curve (the 28-day mortar compressive strength (Y) of the test sample low-carbon mixed cement for concrete) with the control level value of the 28-day mortar compressive strength. As mentioned above, the "control level value for 28-day mortar compressive strength" refers to the 28-day mortar compressive strength of a low-carbon concrete blended cement in which the components are mixed in the designed ratio. In principle, the components are mixed in the factory to obtain a practical mix in the hope of obtaining the 28-day mortar compressive strength confirmed during design. If the predicted value of the practical mix is ​​the same as the control level value, it can be assumed that there was no measurement error and that the mixed cement was produced as designed. In addition, if the predicted value of the practical mix is ​​within the allowable range of, for example, ±5% of the control level value, if the predicted value falls outside that range, the quality can be adjusted by mixing the mixed materials.

[0036] The above method allows the quality of the low-carbon mixed cement for concrete of the test sample to be judged in a short period of time (for example, 1 to 3 days). In particular, the quality of the specific physical property of 28-day mortar compressive strength can be judged numerically, allowing for more accurate quality judgment than ever before.

[0037] <Method of manufacturing blended cement for low-carbon concrete> The method for producing a mixed cement for low-carbon concrete of the present invention is a method for producing a mixed cement for low-carbon concrete, in which the content of Portland cement in the mixed cement is more than 0 mass% and 55 mass% or less, A mixing step of mixing the Portland cement and the mixed material to obtain a low-carbon concrete mixed cement; a quality assessment step of assessing the quality of the low-carbon concrete mixed cement obtained in the mixing step using the quality assessment method for low-carbon concrete mixed cement of the present invention; has. That is, while producing low-carbon mixed cement for concrete in the mixing process, the low-carbon mixed cement for concrete is treated as "test sample low-carbon mixed cement for concrete" in the quality assessment method for low-carbon mixed cement for concrete of the present invention, and the physical property value (X) is determined to predict the 28-day mortar compressive strength (Y) of the test sample, thereby assessing the quality.

[0038] As described above, by using the quality assessment method for low-carbon mixed cement for concrete of the present invention, the quality of the produced low-carbon mixed cement for concrete can be assessed accurately in a short period of time.

[0039] As described above, the mixed cement for low-carbon concrete produced in the mixing step contains Portland cement in an amount of more than 0 mass% and not more than 55 mass%. The Portland cement is preferably one or more selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement. The mixed material is preferably one or more selected from the group consisting of ground granulated blast furnace slag, fly ash, silica fume, an expansive material, and biomass incineration ash.

[0040] The means for mixing the components in the mixing step is not particularly limited. Examples include a mixer, a ball mill, a Roche mill, an air blending silo, etc. The mixing time can be set within a range that is deemed to be sufficient mixing in normal cement production. EXAMPLES

[0041] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples in any way.

[0042] <Ingredients used in the manufacture of blended cement> (1) Portland cement Ordinary Portland cement (c1) (manufactured by Sumitomo Osaka Cement Co., Ltd.) -High-early-strength Portland cement (c2) (manufactured by Sumitomo Osaka Cement Co., Ltd.) (2)Mixed materials Granulated blast furnace slag powder (m1) (manufactured by S-ment Chubu Co., Ltd., product name: S-ment) Fly ash (m2) (manufactured by Techno Chubu Co., Ltd., Type II product as specified in JISA6201) Silica fume (m3) (Elkem, product name: 920D)

[0043] Example 1 Example 1 assumes that blended cement A, which is made in a factory using ordinary Portland cement (c1), ground granulated blast furnace slag (m1), fly ash (m2), and silica fume (m3) in a mass ratio of c1:m1:m2:m3 = 35:40:20:5.

[0044] (Production of mixed cement for calibration curve) Ordinary Portland cement, ground granulated blast furnace slag, fly ash, and silica fume were mixed in the proportions shown in the "Mixture A1" to "Mixture A6" columns of Table 1 to produce six types of mixed cements for calibration curves, A1 to A6.

[0045] (Production of blended cement A) Ordinary Portland cement, ground granulated blast furnace slag, fly ash, and silica fume were mixed in the proportions shown in the "Design A" column of Table 1 to produce blended cement A for measuring the control level values.

[0046] Example 2 Example 2 assumes the case where blended cement B, which is made in a factory using high-early-strength Portland cement (c2), ground granulated blast-furnace slag (m1), fly ash (m2), and silica fume (m3) in a mass ratio of c2:m1:m2:m3 = 20:55:20:5.

[0047] (Production of mixed cement for calibration curve) Six types of mixed cements for calibration curves B1 to B6 were produced by mixing high-early-strength Portland cement, ground granulated blast-furnace slag, fly ash, and silica fume in the mixing ratios shown in the "Mixture B1" to "Mixture B6" columns of Table 2.

[0048] (Production of blended cement B) High early strength Portland cement, ground granulated blast furnace slag, fly ash, and silica fume were mixed in the proportions shown in the "Design B" column of Table 2 to produce blended cement B for measuring the control level values.

[0049] <Measurement of physical properties (X) and 28-day mortar compressive strength (Y)> The physical properties (X) and 28-day mortar compressive strength (Y) of the blended cement A, the blended cements A1 to A6 for calibration curves, the blended cement B, and the blended cements B1 to B6 for calibration curves were measured by the following method.

[0050] 1. Physical property value (X) The physical properties (X) measured were (i) the one-day strength of mortar that had been accelerated cured by heating, (ii) the hydration reaction rate of cement paste that had been accelerated cured by heating after one day, and (iii) the accumulated heat generation after one day from the start of accelerated curing by heating.

[0051] (i) One-day strength of mortar accelerated by heating Calcium chloride was added to each mixed cement at an external ratio of 1% by mass, and the components were mixed in a ratio of 340g mixed cement (including calcium chloride), 204g water, and 1350g sand (water / mixed cement (including calcium chloride) mass ratio was 0.6). Standard sand conforming to JIS R 5201:2015 "Physical test methods for cement" was used. The kneaded material was placed into a mortar formwork conforming to JIS R 5201:2015 "Physical Testing Methods for Cement". The formwork was sealed in a plastic bag and placed in a 40°C thermostatic chamber for curing for 24 hours, after which it was removed from the mold and the compressive strength of the mortar was measured. The results are shown in Tables 1 and 2 in the column "Accelerated 1-day mortar compressive strength."

[0052] (ii) Hydration rate of cement paste after accelerated curing by heating after one day Calcium chloride was added to each mixed cement in an amount of 1% by mass, and water was mixed so that the mass ratio of water / mixed cement (including calcium chloride) was 0.28 to obtain a kneaded product. The kneaded product was placed in a container, sealed, and cured at 45°C for 24 hours. The mortar was then removed from the container and crushed so that all of the mortar passed through a sieve with a particle size of 1 mm. The crushed product was dried at 70°C for 1 hour, and the dried product was weighed. The dried product was ignited at 750°C for 30 minutes, and then weighed to determine the weight loss. The results are shown in the "Accelerated Ignition Loss" column of Tables 1 and 2.

[0053] (iii) Accumulated heat generation one day after the start of accelerated curing by heating 10 g of each mixed cement was weighed into a special sample cup, and 5 g of water for pouring was placed in a conduction calorimeter manufactured by Tokyo Riko Co., Ltd. The integrated heat of hydration (integrated heat generation) was measured 24 hours after pouring water at a set temperature of 45°C. The results are shown in the "Accelerated daily calorific value" column of Tables 1 and 2.

[0054] 2.28-day mortar compressive strength (Y) The 28-day mortar compressive strength of each blended cement mortar was measured in accordance with JIS R 5201:2015 "Physical testing methods for cement." The results are shown in the "28-day mortar compressive strength" column of Tables 1 and 2.

[0055] [Table 1]

[0056] 28-day mortar compressive strength (Y) of mixes A1 to A6 (N / mm 2 ) on the vertical axis (y), and the physical properties (X) of mixes A1 to A6 [accelerated ignition loss (%), accelerated 1-day mortar compressive strength (N / mm 2 ) or accelerated daily calorific value (J / g) on ​​the horizontal axis (x) to create three types of calibration curves. The calibration curve for 28-day mortar compressive strength and accelerated ignition loss was y=2.3849x-7.6833 (coefficient of determination, R 2 =0.9372); The calibration curve for 28-day mortar compressive strength and accelerated 1-day mortar compressive strength is y=1.5099x+0.1213 (coefficient of determination, R 2 =0.9246); The calibration curve for 28-day mortar compressive strength and accelerated heat generation in 1 day was y=0.3281x-34.177 (coefficient of determination, R 2 =0.9259) It was. Three calibration curves based on the above blends A1 to A6 are shown in FIG. 1 to FIG.

[0057] The value of "28-day mortar compressive strength" in "Design A" in Table 1 is the "control level value of 28-day mortar compressive strength" in Example 1, and the tolerance of the strength estimate value was set to ±5% in Example 1. That is, the tolerance range of the 28-day mortar compressive strength in Example 1 is 35.7±1.79 N / mm 2 The range is 33.9 to 37.5 N / mm 2 It becomes. For example, the accelerated mortar compressive strength of the actual mixture (test sample) produced at the mixing factory was measured and found to be 24.8 N / mm 2 If so, the 28-day mortar compressive strength (Y) of the actual mixture is 35.6 N / mm 2 is predicted and is found to be within the acceptable range. For example, when the accelerated ignition loss (hydration reaction rate) of the actual mixture (test sample) manufactured at the mixing factory is measured and found to be 17.8%, the 28-day mortar compressive strength (Y) of the actual mixture is 34.8 N / mm 2 is predicted and is found to be within the acceptable range. Furthermore, for example, when the accelerated one-day heat value of the actual mixture (test sample) manufactured at the mixing factory is measured and found to be 218 J / g, the 28-day mortar compressive strength (Y) of the actual mixture is found to be 37.3 N / mm 2 is predicted and is found to be within the acceptable range.

[0058] [Table 2]

[0059] 28-day mortar compressive strength (Y) of mixes B1 to B6 (N / mm 2 ) on the vertical axis (y), and the physical properties (X) of mixes B1 to B6 [accelerated ignition loss (%), accelerated 1-day mortar compressive strength (N / mm 2 ) or accelerated daily calorific value (J / g) on ​​the horizontal axis (x) to create three types of calibration curves. The calibration curve for 28-day mortar compressive strength and accelerated ignition loss was y=1.0626x+13.445 (coefficient of determination, R 2 =0.8687); The calibration curve for 28-day mortar compressive strength and accelerated 1-day mortar compressive strength is y=0.9464x+10.145 (coefficient of determination, R 2 =0.9312); The calibration curve for 28-day mortar compressive strength and accelerated heat generation in 1 day was y=0.1763x-0.3161 (coefficient of determination, R 2 =0.9262) It was. Three calibration curves based on the above blends B1 to B6 are shown in FIG. 4 to FIG.

[0060] The value of "28-day mortar compressive strength" in "Design B" in Table 2 is the "control level value of 28-day mortar compressive strength" in Example 2, and the tolerance of the strength estimate value was set to ±5% in Example 2. That is, the tolerance range of the 28-day mortar compressive strength in Example 2 is 31.0±1.6 N / mm 2 The range is 29.5 to 32.6 N / mm 2 It becomes. For example, the accelerated mortar compressive strength of the actual mixture (test sample) produced at the mixing factory was measured and found to be 21.2 N / mm 2 If so, the 28-day mortar compressive strength (Y) of the actual mixture is 30.2 N / mm 2 is predicted and is found to be within the acceptable range. For example, when the accelerated ignition loss (hydration reaction rate) of the actual mixture (test sample) manufactured at the mixing factory is measured and found to be 17.2%, the 28-day mortar compressive strength (Y) of the actual mixture is 31.7 N / mm2 is predicted and is found to be within the acceptable range. Furthermore, for example, when the accelerated one-day heat value of the actual mixture (test sample) manufactured at the mixing factory is measured and found to be 173 J / g, the 28-day mortar compressive strength (Y) of the actual mixture is found to be 30.2 N / mm 2 is predicted and is found to be within the acceptable range.

Claims

1. A method for evaluating the quality of a mixed cement for low-carbon concrete, the mixed cement having a Portland cement content of more than 0% by mass and not more than 55% by mass, comprising: The 28-day mortar compressive strength (Y) of a plurality of calibration curve mixed cements containing the Portland cement and the mixed material and varying the content ratio of the mixed material; A correlation between the 28-day mortar compressive strength (Y) of the calibration curve mixed cement and a physical property value (X) of the calibration curve mixed cement accelerated cured by heating is previously obtained, A method for assessing the quality of a low-carbon mixed cement for concrete, comprising: determining a physical property value (X) of a test sample of low-carbon mixed cement for concrete, predicting a 28-day mortar compressive strength (Y) of the test sample, and assessing the quality of the test sample of low-carbon mixed cement for concrete by comparing the 28-day mortar compressive strength (Y) of the test sample with a control level value of the 28-day mortar compressive strength.

2. 2. The quality assessment method for a low-carbon mixed cement for concrete according to claim 1, wherein the physical property value (X) is measured by mixing a hardening accelerator with the calibration curve mixed cement and the test sample of the low-carbon mixed cement for concrete.

3. The method for evaluating the quality of a mixed cement for low-carbon concrete according to claim 1 or 2, wherein the conditions of accelerated curing by heating of the mixed cement for calibration curve preparation are 30 to 70°C and 6 to 24 hours.

4. 3. The quality evaluation method for a low-carbon mixed cement for concrete according to claim 1 or 2, wherein the physical property value (X) is one or more selected from the group consisting of (i) one-day strength of mortar subjected to accelerated curing by heating, (ii) hydration reaction rate of cement paste subjected to accelerated curing by heating after one day, and (iii) accumulated heat generation after one day from the start of accelerated curing by heating.

5. 3. The method for evaluating the quality of a mixed cement for low-carbon concrete according to claim 1 or 2, wherein the Portland cement is one or more selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement.

6. The quality assessment method for mixed cement for low-carbon concrete according to claim 1 or 2, wherein the mixed material is one or more selected from the group consisting of ground granulated blast furnace slag, fly ash, silica fume, expansive agent and biomass incineration ash.

7. 3. The quality assessment method for mixed cement for low-carbon concrete according to claim 2, wherein the hardening accelerator is one or more selected from the group consisting of calcium chloride, potassium chloride, sodium chloride, sodium thiocyanate and calcium formate.

8. A method for producing a mixed cement for low-carbon concrete, the mixed cement having a Portland cement content of more than 0% by mass and not more than 55% by mass, comprising: A mixing step of mixing the Portland cement and the mixed material to obtain a low-carbon concrete mixed cement; a quality assessment step of assessing the quality of the low-carbon concrete mixed cement obtained in the mixing step by using the quality assessment method for the low-carbon concrete mixed cement according to claim 1 or 2; A method for producing a low-carbon mixed cement for concrete comprising the steps of:

9. 9. The method for producing a mixed cement for low-carbon concrete according to claim 8, wherein the Portland cement is at least one selected from the group consisting of ordinary Portland cement and high-early-strength Portland cement.

10. 9. The method for producing a mixed cement for low-carbon concrete according to claim 8, wherein the mixed material is one or more selected from the group consisting of ground granulated blast furnace slag, fly ash, silica fume, expansive agent, and biomass incineration ash.

Citation Information

Patent Citations

  • Method for rapidly determining compressive strength ratio of ground limestone powder

    CN111307588A

  • Method and equipment for testing accelerated strength of concrete

    JP1977056124A

  • Mixed cement and method of producing concrete

    JP2014144878A

  • Quality control method for fresh concrete and method for manufacturing concrete structure

    JP2016205940A

  • Permanent magnet rotary electric machine

    JP1986098143A